Matharpacady-14.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
This old home, at 9 Matharpacady, has batwing doors (double swinging doors) at the entrance, preserving its historical character and charm. The lintel above the door is decorated with colourful tiles with floral motifs, each different from the rest.